Adherence to oxidative balance score is inversely associated with the prevalence of stroke: results from National Health and Nutrition Examination Survey 1999–2018 - Chen, Jiarui; Liu, Jianjian; Gu, Zhaowen; Fan, Jiayong; Lei, Shuxin; Zhang, Qia; Pan, Kai; Wang, Yongjie (Frontiers in Neurology, 2024)
Introduction The relationship between oxidative balance score (OBS), an emerging integrative metric for assessing individual redox homeostasis, and the prevalence of stroke in the general population remains unknown. We aimed to explore these relationships in the National Health and Nutrition Examination Survey (NHANES). We investigated the relationship between the oxidative balance score (OBS) and stroke prevalence using NHANES data from 1999–2018. Methods We included eligible individuals from NHANES 1999–2018. OBS calculations were based on previously validated methods, and stroke diagnoses were based on self-reports in questionnaires. Multivariable logistic regression analyses were used to examine the independent associations of overall, dietary, and lifestyle OBS with stroke prevalence. In addition, restricted cubic spline (RCS), stratified analysis, and sensitivity analysis were used. Results We included 25,258 participants aged 20–85 years, in which the prevalence of stroke was 2.66%. After adjusting for all confounders, overall and dietary OBS, but not lifestyle OBS, were inversely associated with the prevalence of stroke [odds ratios and 95% confidence intervals of 0.97 (0.96, 0.99) and 0.98 (0.96, 0.99) for overall and dietary OBS, respectively, both p < 0.05]. In addition, there was a dose-response relationship between overall and dietary OBS and stroke prevalence. The RCS showed that these relationships were linear. Stratified analyses indicated that socioeconomic status (SES) significantly influenced the relationship between all OBS and stroke prevalence. Conclusion Dietary OBS, but not lifestyle OBS, had an inverse relationship with the prevalence of stroke in the general population. SES significantly influenced the protective effect of OBS against stroke. These findings emphasize the importance of integrated antioxidant properties from diet for stroke prevention.